Istikhdāmu al-Ṭarīqah al-Īhāiyah wa Fa’āliyatuhā fī Tanmiyati Mahārati al-Kalām ‘alā Ṭalabati Jāmi’ati Maulānā Mālik Ibrāhīm al-Islāmiyah al-Hukūmiyah Malang - Jumriyah, Jumriyah (Journal of Language Intelligence and Culture, 2020)
The Suggestopedia method consists of a series of recommendations based on the education of the science of suggestion described by Lozanov that suggestion is "science relating to the study of the effects of organizational irrationality and the unconscious, or both," which respond to people continuously. Then the problems in this study: (2) How effective is the use of the Suggestopedia method to develop speaking skills in aspects of pronunciation, vocabulary, sentence structure, and fluency. The research methodology used in this study is quantitative empirical and qualitative analysis. Then the researchers restricted the experimental and control groups to the E-6 class in the Arabic intensive program at Maulana Malik Ibrahim State Islamic University of Malang for the 2013-2014 academic year with 36 students. The researcher used the analysis of the T-test to reveal the results of the pre-test and post-test. And the results of this study were: (1) the results of t0 in the pronunciation aspect of the experimental group 51.63 this value is greater than the control group that is 0.129 (2) the results of t0 on aspects of the experimental group vocabulary 24,713 this value is greater than the control group that is 1.193. (3) the results of t0 in the sentence structure aspect of the experimental group 8.36 this value is greater than the control group that is 0.383 (4) the results of t0 in the smoothness aspect of the experimental group 8.475 this value is greater than the control group 0 (5) results of t0 in the pre-test and post-test experimental group was greater by 22.695 than in the control group that was 0.968.